Mosaic 1 : - Hanreddy, Jami (McGraw-Hill Contemporary, 2002)
"Interactions Mosaic 4th Edition" is the newly expanded five-level, four-skill comprehensive "ESL/ELT" series for academic students. The new edition, for beginners to advanced learners, incorporates interactive and communicative activities while still focusing on skill building to prepare students for academic content. Reading, writing, listening and speaking, as well as grammar are thoroughly presented in each strand.